1‐Amino‐3‐(1H‐1, 2, 3‐triazol‐1‐yl)propylphosphonates as Acyclic Analogs of Nucleotides. Issue 7 (6th April 2014) - Głowacka, Iwona E.; Balzarini, Jan; Piotrowska, Dorota G.
<x xml:space="preserve">Abstract</x> A new series of 1‐amino‐3‐(1H‐1, 2, 3‐triazol‐1‐yl)propylphosphonates (R)‐ and (S)‐16 were obtained from enantiomerically pure (R)‐ and (S)‐1‐tert‐butoxycarbonyl (Boc)‐amino‐3‐azidopropylphosphonates and N‐propargylated nucleobases in good yields. All 1, 2, 3‐triazolylphosphonates (R)‐ and (S)‐16 were evaluated for their activities against a broad range of DNA and RNA viruses. Compound (R)‐16g (B = 3‐acetylindole) was moderately active against vesicular stomatitis virus in HeLa cell cultures (EC50 = 45 µM). In addition, (S)‐16c (B = adenine), (R)‐16f (B = N3‐Bz‐benzuracil), (R)‐16g (B = 3‐acetylindole), and (R)‐16h (B = 5, 6‐dimethylbenzimidazole) were cytotoxic toward Crandell‐Rees feline kidney (CRFK) cells (CC50 = 2.9, 45, 72, and 96 µM, respectively). Compounds (R)‐16g, (S)‐16g, and (S)‐16h were slightly cytostatic to different tumor cell lines.